The Influence of Embeddedness of Socio-Economic Status and Self-Control on Consumptive Behavior of Students (at MA Khazanah Kebajikan Ciputat) - Kharisma Danang Yuangga; Neneng Susanti (Universitas Negeri Makassar, 2019)
In Economic Sociology, social attachment is something that cannot be denied, especially in economic behavior. The purpose of this study was to determine the embandedness of socio-economic status and self-control of the consumptive behavior of students at the MA Khazanah Kebajikan Ciputat. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling using the method of saturated sampling technique with a sample of 73 respondents. The analysis tool uses validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are the embandedness of socio-economic status has a positive and significant effect on the consumptive behavior of students by 41.7%. Hypothesis testing is obtained tcount> ttable or (7.133> 1.994), so that H0 is rejected and H1 is accepted, meaning there is a positive and significant influence between the embandedness of socio-economic status on the consumptive behavior of students at MA Khazanah Kebajikan Ciputat Office. Self-control has a positive and significant effect on student consumptive behavior by 40.2%. Hypothesis testing is obtained tcount> ttable or (6.906> 1.994) so that H0 is rejected and H2 is accepted meaning that there is a positive and significant influence between self-control on the consumptive behavior of students on. A simultaneous test of the embandedness of socio-economic status and self-control has a positive and significant effect on the consumptive behavior of students with a contribution of 48.4%, while the remaining 53.2% is influenced by other factors. Hypothesis testing obtained the value of Fcount> Ftable or (39.814> 2.740), thus Ho is rejected and H3 is accepted. This means that there are positive and significant simultaneous influences between embandedness of socio-economic status and self-control on the consumptive behavior of students at the MA Khazanah Kebajikan Ciputat